Nazwy w dyskursie – w kontekście koncepcji wtórnej oralności - Rutkowski, Mariusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
In the paper, the chosen cases of using the proper names revealing the residual orality in the term of Walter Ong are presented. What is characteristic, proper names are used in the extensive, aggregative formulas, in their full-forms rather than in potential abbreviated forms (e.g. name of Polish political party Prawo i Sprawiedliwość instead its abbreviation PiS). Another feature is formulas with the stable collocations, used for strengthen the persuasive value of the utterances. Another residual orality features are: agonistically toned and homeostatic – proper names in those utterances may assist in the political rhetoric, or ever strengthen the creation of the new political myths.